PERBEDAAN KEMAMPUAN LITERASI NUMERASI MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN PROJECT BASED LEARNING (PjBL) PADA POKOK BAHASAN PROGRAM LINEAR - Khairi Siregar, Alfi; Maysarah, Siti (Universitas Swadaya Gunung Jati., 2024)
This research aims to see the differences in the numeracy literacy abilities of students taught using the Problem Based Learning learning model in class XI MIA 2 and Project Based Learning in class XI MIA 2 in Linear Program material. This research uses an experimental method with a post-test two experimental group design with a population of 5 classes XI MIA totaling 179 students and a sample of 2 classes namely XI MIA 1 totaling 36 students and indicator of numeracy literacy ability. The research results showed that there was no significant difference between classes XI MIA 1 and XI MIA 2 regarding students' numeracy literacy abilities in Linear Program material.